A Critical Review of International Students’ Adjustment Research from a Deleuzian Perspective - Vasilopoulos, Gene (Journal of International Students, 2016)
The author in this paper critically reviews recent literature on international student language and adjustment to Western Anglophone universities. Two streams of research are discussed: the problem-solving approach guided largely by positivist epistemologies and quantitative methodologies contrasted to the post-structuralist language and identity framework employing qualitative methods. Limitations to both perspectives include the reliance on fixed constructs of language and adjustment, the isolation of interrelated variables, the attempt to establish linear correlational/causative relationships, the essentialization of identity, and the inability to explain change and variance. Deleuzian ontology of ‘becoming’ and assemblage is put forward as a framework to better understand the complexity, unpredictability, and ever-changing process that international students face when co-adapting to the their new academic community.